Genetic effects on educational attainment in Hungary. Issue 1 (29th November 2021) - Ujma, Péter P.; Eszlári, Nóra; Millinghoffer, András; Bruncsics, Bence; Török, Dóra; Petschner, Péter; Antal, Péter; Deakin, Bill; Breen, Gerome; Bagdy, György; Juhász, Gabriella
Abstract: Introduction: Educational attainment is a substantially heritable trait, and it has recently been linked to specific genetic variants by genome‐wide association studies (GWASs). However, the effects of such genetic variants are expected to vary across environments, including countries and historical eras. Methods: We used polygenic scores (PGSs) to assess molecular genetic effects on educational attainment in Hungary, a country in the Central Eastern European region where behavioral genetic studies are in general scarce and molecular genetic studies of educational attainment have not been previously published. Results: We found that the PGS is significantly associated with the attainment of a college degree as well as the number of years in education in a sample of Hungarian study participants ( N = 829). PGS effect sizes were not significantly different when compared to an English ( N = 976) comparison sample with identical measurement protocols. In line with previous Estonian findings, we found higher PGS effect sizes in Hungarian, but not in English participants who attended higher education after the fall of Communism, although we lacked statistical power for this effect to reach significance. Discussion: Our results provide evidence that polygenic scores for educational attainment have predictive value in culturally diverse European populations. Abstract : We found that polygenic scores (PGS) associated with educational attainment (EA) in an international genome‐wide association study are also associated with EA in Hungary, despite historic, societal and economic differences between this country and those in which the PGS was discovered. Our results demonstrate the general validity of the PGS.